Gorlin syndrome - Basanti Devi (Indian Journal of Dermatology, 2013)
Gorlin Syndrome, a rare genodermatosis, otherwise known as Nevoid basal cell carcinoma syndrome (NBCCS) is a multisystem disease affecting skin, nervous system, eyes, endocrine glands, and bones. It is characterized by multiple basal cell carcinomas, palmoplantar pits, jaw cysts, and bony deformities like kyphoscoliosis and frontal bossing. We would like to report a case of Gorlin syndrome with classical features, as this is a rare genodermatosis.